Optical imaging of finger for blood pressure monitoring of the driver - Mohammad Motasim Bellah (19774569) (2015)
Cardiovascular diseases (CVDs) are number one reason for human mortality around the world (Fig. 1) [1]. Pulse pressure (PP) and pulse rate (PR) are considered as the two most vital physiological markers for CVDs like myocardial infarction, cardiac arrhythmia, and heart failure. Currently, long-term PP and PR analysis is not possible due to the lack of systems that can frequently measure the data over a period of time. Motor vehicle drivers with known CVDs are at higher risk due to traffic air pollution. This paper presents our work on an inexpensive and readily deployable approach that keeps track of PP and PR with simple cameras. The computation of PP and PR makes the real-time monitoring possible. The approach makes it highly customizable and ready for on-the-go use in field by drivers, construction zone workers, healthcare workers, law enforcement agencies, etc. The video recordings of fingertips were made using a cellphone camera. The analysis extracted the pulse pressure, which was the difference between systolic and diastolic pressures, and pulse rate. The PP measured with this system was compared with a standard off-the-shelf tool. The comparison showed high accuracy. The measurement of PRs also showed a high level of reliability in comparison to the standard tool. The fundamental concept of the technology depended on the measurement of blood quantity in the fingertip arteries. The amount of blood on fingertips was different during systolic and diastolic phases. This created light intensity variations, which were extracted by analyzing the video frames. A simple embodiment of this approach can be in the dashboard of cars with a camera to create short high-resolution videos of fingertips. The doctors can remotely monitor their patients through a standard computer interface. The patients can also be trained to interpret the results of the measurement. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.39